2015
DOI: 10.1371/journal.pone.0120236
|View full text |Cite
|
Sign up to set email alerts
|

Optomotor-Blind Negatively Regulates Drosophila Eye Development by Blocking Jak/STAT Signaling

Abstract: Organ formation requires a delicate balance of positive and negative regulators. In Drosophila eye development, wingless (wg) is expressed at the lateral margins of the eye disc and serves to block retinal development. The T-box gene optomotor-blind (omb) is expressed in a similar pattern and is regulated by Wg. Omb mediates part of Wg activity in blocking eye development. Omb exerts its function primarily by blocking cell proliferation. These effects occur predominantly in the ventral margin. Our results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 89 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…Proliferation of glia along the NER of A8/9 was assessed in third instar larvae using the phospho-histone H3 (pH3) antibody, which labels mitotic cells. Specificity of the pH3 antibody was confirmed by immunostaining third instar eye imaginal discs, which revealed a pattern of pH3 immunostaining consistent with previously published studies ( S1 Fig ) [ 42 ]. Along the A8/9 peripheral nerve, approximately 90% of glial cells were labeled with the pH3 antibody in the repo -Gal4 and repo -Gal4> dcr2 control samples ( Fig 4 ).…”
Section: Resultssupporting
confidence: 88%
“…Proliferation of glia along the NER of A8/9 was assessed in third instar larvae using the phospho-histone H3 (pH3) antibody, which labels mitotic cells. Specificity of the pH3 antibody was confirmed by immunostaining third instar eye imaginal discs, which revealed a pattern of pH3 immunostaining consistent with previously published studies ( S1 Fig ) [ 42 ]. Along the A8/9 peripheral nerve, approximately 90% of glial cells were labeled with the pH3 antibody in the repo -Gal4 and repo -Gal4> dcr2 control samples ( Fig 4 ).…”
Section: Resultssupporting
confidence: 88%
“…Immunostaining of the eye discs carrying a STAT92E activity reporter, which contains 10 STAT92E binding sites linked to a GFP reporter gene (Bach et al, 2007), showed punctate GFP expression in the posterior part of the eye disc, which overlaps with the carpet glia (Figure 6C). We further examined the expression of a modified STAT92E activity reporter whose GFP is nucleus localized (Tsai et al, 2015) and found GFP expression in the carpet nuclei (Figure 6D). In addition, active JAK-STAT signaling was also found in the migratory RBGs and the PRs in the posterior part of the eye disc (Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
“…The different UAS-dsRNA flies used in this study were obtained from the Vienna Drosophila Resource Center (VDRC) or the TRiP collection (BDSC): UAS-kay dsRNA (BDSC #27722, #31391), UAS-Rho1 dsRNA (BDSC #9909, #9910), and UAS-path dsRNA (VDRC #100519). Other fly lines used were UAS-Upd3 (Houtz et al, 2017; provided by Dr. Yu-Chen Tsai), 10xSTAT-GFP (Bach et al, 2007; provided by Dr. Y. Henry Sun), and 10xSTAT-GFP-nls (Tsai et al, 2015; provided by Dr. Yu-Chen Tsai).…”
Section: Methodsmentioning
confidence: 99%
“…We also used the 10XSTAT-GFP reporter to determine whether the JAK-STAT pathway, which is activated by Upd1-3, is affected by dBRWD3 in PcG mutant cells [ 40 , 41 ]. In contrast to the weak and uniform expression observed in wild-type antennal discs ( Fig 3L and 3M , arrows), the GFP signal was much higher in Scm D1 mutant clones ( Fig 3N ), likely due to up-regulation of upd1-3 .…”
Section: Resultsmentioning
confidence: 99%